DURATION AND TIMING OF SPAWNING SEASONS IN MARINE TELEOSTS: A BIOGEOGRAPHICAL APPROACH - Fayakun Satria (Research Center for Fisheries, 2006)
The duration and timing patterns of spawning seasons among marine teleosls tishes over broad geographic ranges from the polars to the equator has been reviewed. The review was based on 206 studies In order to evaluale potenlial patterns of the length or timing of spawning seasons in relation to tatitude, habitats and taxonomic groupings patterns.